Evaluation of the Corrosion Resistance of AISI 316l Steel Subjected to Severe Deformation Using the Groove Pressing Technique - Aragón-Lozano, Walter Yesid; Fernández-Vega, Luis Felipe; Higuera-Cobos, Oscar Fabián; Tristancho-Reyes, José Luis; Pedraza-Yepes, Cristian Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In this investigation, samples of AISI 316L steel were subjected to severe plastic deformation by the groove pressing (GP) technique using 2 dies A2 type tool steel dies with dimensions of 96 mm X 96 mm, a corrugated die with 2 mm teeth and 45° angle and a flat die. Each pass through the GP die includes 2 states of corrugated and 2 states of straightening with a 180° rotation between each of them. This configuration provides the material with an equivalent theoretical deformation per pass of ε~1.16. The material was deformed by 4 passes per GP to an equivalent deformation of ε~4.64. Prior to the deformation, the specimens were subjected to an annealing heat treatment for 1 hour at 1000 °C with water cooling, in order to eliminate the lamination texture. The annealed and deformed material was characterized chemically and microstructurally by X-ray fluorescence and scanning electron microscopy, respectively. In order to evaluate the corrosion behavior of the material, linear polarization resistance and analysis by Tafel plot were used in a 0.6 M NaCl solution for 0 and 24 hours. The results show an atypical behavior regarding the corrosion resistance of AISI 316L steel. An increase in corrosion resistance of 45% of the material was observed after 4 passes per GP compared to annealed material (0 passes).